(untitled) (Scientific journal of the Fergana State University, 2024)
The article presents a study of flavonoids in a biological additive from anise and coriander using high-performance liquid chromatography. The flavonoids dihydroquercetin, luteinin, rutin, seneroside, quercetin and salidroside were identified as part of the biological additive. The total amount of flavonoids was 111.85 mg/g. The flavonoids rutin, luteolin and quercetin are found in large quantities.